Active interaction control of civil structures. Part 2 MDOF systems. - Zhang, Yunfeng
In this paper, the performance of active interaction control (AIC) algorithms is assessed within the context of two realistic building models. The AIC control approach is proposed as a semi-active means of mitigating the structural response during large earthquakes. To implement the AIC control algorithms into MDOF systems, the modal control (MC) approach that directs the control effort to certain dominant response modes is formulated and utilized herein. Two structures, a 3 storey building and a 9 storey steel framed benchmark building controlled by the AIC algorithms are analysed for two historical earthquake records. The results of numerical simulation verify the efficacy of the AIC control algorithms in controlling vibration of building structures during large earthquakes.
Keywords: Structural control; Semi-active control; Seismic response